Effects of occlusal hypofunction on root surface area in patients exhibiting anterior crossbite in skeletal Class III malocclusion: a CBCT study - Nawa Ponyiam; Wikanda Khemaleelakul; Thanapat Sastraruji; Kachaphol Kuharattanachai; Kanich Tripuwabhrut (Clinical and Investigative Orthodontics)
Purposes To evaluate and compare the effects of occlusal hypofunction on root surface areas (RSAs) of permanent teeth in patients with Class III and Class I skeletal relationships.Materials and Methods Thirty-two CBCT images of all permanent maxillary and mandibular teeth, except the third molars, from 16 patients (mean age 23.71 ± 4.04 years) exhibiting Class III skeletal relationships and 16 patients (mean age 24.53 ± 4.91 years) exhibiting Class I skeletal relationships were imported into the Mimics software version 15.01. The outer boundaries of the teeth in two-dimensional images were manually identified on each CBCT slice along the coronal, sagittal, and axial planes to construct three-dimensional models. The tooth models were transferred into 3-matic version 7.01 to specify cementoenamel junctions and calculate RSAs. Intra-examiner reliability was assessed using the intra-class correlation coefficient. The RSAs of each tooth type from the two groups were illustrated and compared using independent t-tests (p < 0.05).Results The RSAs of the maxillary second molars in the skeletal Class III group were significantly higher than those in the skeletal Class I group. There were no significant differences in RSAs between the two groups regarding other tooth types.Conclusions Young adults exhibiting Class III skeletal relationships exhibited significantly greater RSAs in the maxillary second molars. This might be related to occlusal hypofunction during dental root formation.